Pilot study of Ixodes ricinus ticks preference for human ABO blood groups using a simple in vitro method - Žákovská, Alena; Janeček, Jan; Nejezchlebová, Helena; Kučerová, Hana Lya (AAEM. Annals of Agricultural and Environmental Medicine, 2018)
INTRODUCTION AND OBJECTIVES: The existence of a blood group preference for ticks is a problem widely discussed among the lay public but often neglected by the scientific community. The Ixodes ricinus tick transmits serious zoonotic diseases such as Lyme borreliosis, tick encephalitis, or anaplasmosis. The preventive strategies include vaccination (if available) and individual measures including the use of repellents and avoidance of risk areas. MATERIAL AND METHODS: Since this topic is relatively neglected in the scientific literature, a simple in vitro method was used. Ticks used in this study were collected in the suburban region of Ruda in Brno, Czech Republic. One hundred active nymphs of the collected ticks were tested for preferences for blood groups, using Petri dishes and blood samples from volunteers. To demonstrate the threat of ticks and the diseases they transmit, the positivity of one of the most abundant zoonosis, Lyme borreliosis, was tested using dark-field microscopy. RESULTS: The results obtained showed that the examined ticks were attracted most by blood group A, whereas the least preferred was group B, which was proved statistically (p <0.05). The mean positivity of collected ticks for the presence of spirochaetes was 9.35%. CONCLUSIONS: The results indicate that the host selection of ticks may be influenced by the physiological or biochemical profile of an individual, such as their blood group. This means that a blood group of an individual can be one of the factors that increase the risk of tick bite and the transmission of dangerous diseases and thus must not be underestimated.
Keywords: určování krevní skupiny a křížové zkoušky; Tick-Borne Diseases; klíště; Ixodes; Humans; lidé; kousnutí klíštětem; zvířata; Animals; Pilot Projects; Female; pilotní projekty; Male; Blood Grouping and Crossmatching; ABO systém krevních skupin; nemoci přenášené klíšťaty; Tick Bites; mužské pohlaví; ženské pohlaví; ABO Blood-Group System